2020
DOI: 10.1016/j.envres.2019.108841
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposures to particulate matter gamma radiation activities and biomarkers of systemic inflammation and endothelial activation in COPD patients

Abstract: Background:We hypothesized that particulate matter (PM) gamma activity (gamma radiation associated with PM) is associated with systemic effects.Objective: Examine short-term relationships between ambient and indoor exposures to PM gamma activities with systemic inflammation and endothelial activation in chronic obstructive pulmonary disease (COPD) patients. Methods:In 85 COPD patients from Eastern Massachusetts, USA from 2012-2014, plasma Creactive protein (CRP), interleukin-6 (IL-6), and soluble vascular cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In good accordance with existing literature, this study found a positive correlation between outdoor exposure to daily average air pollutants PM2.5, PM10, NO 2 , SO 2 , CO concentrations, and daily new COVID-19 confirmed (DNC) and deaths (DND) cases ( Shao et al, 2022 , Li et al, 2020 , Domingo et al, 2020 , Marquès et al, 2021 , Frontera et al, 2020 , Zoran et al, 2020a , Zoran et al, 2020b , Islam et al, 2021 , Huang et al, 2020 , Huang et al, 2020 , Amin et al, 2020 , Hassanzadeh et al, 2020 ; Zhu et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In good accordance with existing literature, this study found a positive correlation between outdoor exposure to daily average air pollutants PM2.5, PM10, NO 2 , SO 2 , CO concentrations, and daily new COVID-19 confirmed (DNC) and deaths (DND) cases ( Shao et al, 2022 , Li et al, 2020 , Domingo et al, 2020 , Marquès et al, 2021 , Frontera et al, 2020 , Zoran et al, 2020a , Zoran et al, 2020b , Islam et al, 2021 , Huang et al, 2020 , Huang et al, 2020 , Amin et al, 2020 , Hassanzadeh et al, 2020 ; Zhu et al, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…If fine particulate matter PM2.5, one of the main contributor to air pollution is considered the fourth leading risk factor for death and disability in the world ( GBD C, 2020 , WHO, 2016 , Xu et al, 2020 ), 222 Rn is the second cause of lung cancer, behind smoking ( Hosoda et al, 2021 ). Joint short-term and chronic exposure to particulate matter and alpha ionizing radiation of 222 Rn substantially increases the risk of respiratory tract illnesses damage ( Huang et al, 2020 , Huang et al, 2020 , Shahbazi-Gahrouei et al, 2013 , Vieira et al, 2019 ; Marsh and Bailey, 2013). Environmental radioactive nuclei from background radon sources (natural terrestrial and extra-terrestrial) can attach to respirable PM, which once inhaled are deposited on the respiratory tract and can translocate into systemic circulation, and contribute to the development of both pulmonary and systemic endothelial dysfunction in human lungs ( Chauhan et al, 2012 , Mohamed et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure to NO 2 has been associated with low birthweight in large cohort studies 38 . This effect may be through direct effects of NO 2 that has entered the maternal circulation or from a systemic inflammatory response induced by contact with NO 2 in the maternal lungs 44 . Either of these responses may induce oxidative stress and DNA damage, which in turn can lead to impaired placental function, 45 most likely through either genomic or mitochondrial DNA damage 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…38 This effect may be through direct effects of NO 2 that has entered the maternal circulation or from a systemic inflammatory response induced by contact with NO 2 in the maternal lungs. 44 Either of these responses may induce oxidative stress and DNA damage, which in turn can lead to impaired placental function, 45 most likely through either genomic or mitochondrial DNA damage. 46,47 Why the early developing placenta could be more susceptible to NO 2 -mediated damage than the placenta later in pregnancy is unclear, but it may be related to a more established ability of the placenta to withstand insults or reduced maternal inflammatory responses as pregnancy progresses.…”
Section: Context Of Study Findingsmentioning
confidence: 99%
“…Exposure to PM 2.5 in the air is significantly associated with an increase in COPD prevalence and an increase in the acute exacerbation risk, hospitalization rate, and mortality of patients with COPD ( 6 , 7 ). Concurrently, exposure to PM 2.5 for a short time could lead to a systemic inflammatory response in patients with COPD ( 8 ). Therefore, it is important to explore the mechanism of PM 2.5 exposures leading to COPD.…”
Section: Introductionmentioning
confidence: 99%